2018
DOI: 10.21475/ajcs.18.12.07.pne1136
|View full text |Cite
|
Sign up to set email alerts
|

Peanut seed yield under influence of fertilizer and biostimulant

Abstract: Nowadays, the search for increase in the crop productivity with high organoleptic, physical and physiological quality of seeds remains one of the main objectives. Considering the importance of peanuts (Arachis hypogaea L.) for Brazilian agriculture and for the production of seeds, it is indispensable to use technological innovations aiming at the advancement of productivity and profitability for the seed producer. This study aimed to evaluate the yield and the components of peanut seed production of cultivar B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
2
Order By: Relevance
“…It's also observed that T5 (peanut husk (55%) + carbonized rice husk (15%) + decomposed rice husk (15%) + topsoil (15%)) displayed the lowest values for all analyzed variables (Table 2), possibly due to the higher percentage of peanut husk in the substrate. The peanut crop is susceptible to fungal attacks, both in the aerial part, stem, and pods, resulting in seed and husk contamination (MELO et al, 2018). In desert rose cultivation, during the germination and initial development phase, high rates of losses due to fungal and bacterial attacks resulting in stem rot are observed.…”
Section: Figurementioning
confidence: 99%
“…It's also observed that T5 (peanut husk (55%) + carbonized rice husk (15%) + decomposed rice husk (15%) + topsoil (15%)) displayed the lowest values for all analyzed variables (Table 2), possibly due to the higher percentage of peanut husk in the substrate. The peanut crop is susceptible to fungal attacks, both in the aerial part, stem, and pods, resulting in seed and husk contamination (MELO et al, 2018). In desert rose cultivation, during the germination and initial development phase, high rates of losses due to fungal and bacterial attacks resulting in stem rot are observed.…”
Section: Figurementioning
confidence: 99%
“…Efeitos positivos do tratamento de sementes com bioestimulante foram constatados em mudas de diversas hortaliças, como alface (ALBUQUERQUE et al, 2009;SOARES et al, 2012), batata-doce (RÓS et al, 2015) e maxixe (OLIVEIRA et al, 2017). Melo et al (2018) notaram que aplicação de bioestimulantes como o Stimulate ® nas sementes tem se mostrado eficaz na promoção do processo de germinação/emergência, proporcionando mais mudas normais e reduzindo significativamente as mudas anormais, fato que ocorreu no presente ensaio.…”
Section: Fvunclassified
“…A utilização de produtos comerciais que contenham a mistura auxina, ácido giberélico e citocinina pode facilitar o emprego dessa técnica, tornando-a mais acessível ao produtor (TECCHIO et al, 2015). Dentre as opções disponíveis atualmente no mercado, o Stimulate ® é um bioestimulante com potencial para ser utilizado, pois atua no crescimento e desenvolvimento vegetal, estimulando a divisão celular, a diferenciação e o alongamento das células, com aumento também da absorção e da utilização dos nutrientes, podendo ser eficiente quando aplicado via semente ou foliar (MELO et al, 2018).…”
Section: Introductionunclassified
“…Soybean production loses occur only when the stress was severe the enough to cause the reduction of stand result in death of the plant . From the moment of removal of the aerial part or the percentage of stress, the plants recover and develop without having their grain production affected (Melo et al, 2018), thus expressing the phenotypic plasticity of the crop soybean and the potential for forage exploration, in addition to grains. Thus, the withdrawal of a percentage of the branches and leaves of soybean plants possibility reduced height, preventing lodging, providing a mechanical harvesting more e cient and does not impair the grain yield (Souza et al, 2013), helping also in improving the harvest and in the best quality of the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…In this aspect, plants such as peanuts, soybeans, sesame, etc., have the potential to supply nutrients to animals, not only grains and seeds, but also plant biomass, as they are rich in nutrients and thus the use of biomass in animal feed would be relevant due to to the signi cant nutritional value ( Melo et al, 2018, Berto et al, 2021, stimulating the production of these crops associated with the use of technologies that allow maximum exploitation without the need to open new areas. Thus, in order to highlight the potential of soybean in the Agreste Meridional region of Pernambuco, the objective is to evaluate the production of soybean plants and regrowth.…”
Section: Introductionmentioning
confidence: 99%